Ion-solvation-induced molecular reorganization in liquid water probed by resonant inelastic soft x-ray scattering - Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (The journal of physical chemistry letters, 2014)
The molecular structure of liquid water is susceptible to changes upon admixture of salts due to ionic solvation, which provides the basis of many chemical and biochemical processes. Here we demonstrate how the local electronic structure of aqueous potassium chloride (KCl) solutions can be studied by resonant inelastic soft X-ray scattering (RIXS) to monitor the effects of the ion solvation on the hydrogen-bond (HB) network of liquid water. Significant changes in the oxygen K-edge emission spectra are observed with increasing KCl concentration. These changes can be attributed to modifications in the proton dynamics, caused by a specific coordination structure around the salt ions. Analysis of the spectator decay spectra reveals a spectral signature that could be characteristic of this structure.
Gesehen am 22.10.2020